Foley catheter used for peritoneal dialysis - Mujaheed Suleman; Mathayo Shadrack; David Msuya; Samwel Chugulu; Kondo Chilonga; Deborah Mchaile; Kajiru Kilonzo; Jay Lodhia (Journal of Pediatric Surgery Case Reports, 2021)
In developing countries surgical management can be challenging due to lack of standard resources hence surgeons should adapt to the available resources to serve the purpose in the appropriate management.Herein we share our experience with two children who presented with acute kidney injury to our centre and were managed by peritoneal dialysis using modified peritoneal dialysis catheters.Due to the lack of resources and affordability surgeons have been forced to improvise the available resources to overcome the challenges in resource-limited settings.